The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/biom12091210
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of the Expression and Localization of Prothymosin α in Human Testis and Its Involvement in Testicular Cancers

Abstract: Prothymosin α (PTMA) is a phylogenetically conserved polypeptide in male gonads of Vertebrates. In Mammals, it is a ubiquitous protein, and, possessing a random-coin structure, it interacts with many other partners, in both cytoplasmic and nuclear compartments. PTMA has been widely studied during cell progression in different types of cancer because of its anti-apoptotic and proliferative properties. Here, we provided the first evidence of PTMA expression and localization in human testis and in two testicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…With the aim of expanding knowledge about the mechanisms of spermatogenesis and human reproduction, we have previously characterized some proteins, such as PTMA ( Venditti and Minucci, 2017 ; Minucci and Venditti, 2022 ; Venditti et al, 2022 ), and two cytoskeleton-related proteins, DAAM1 ( Minucci and Venditti, 2022 ; Pariante et al, 2016a ; Venditti et al, 2020b ; c ; Venditti et al, 2021a ) and PREP ( Santillo et al, 2019 ; Venditti and Minucci, 2019 ; Venditti et al, 2020b ; Venditti et al, 2021a ; Minucci and Venditti, 2022 ), in the testis, suggesting their involvement in the proliferative and differentiative stages of gametogenesis. In particular, PTMA, one of the most acidic mammalian polypeptides (3.5 isoelectric point), is an anti-apoptotic factor associated with post-meiotic GC progression and SPZ interaction with the oocyte ( Venditti and Minucci, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the aim of expanding knowledge about the mechanisms of spermatogenesis and human reproduction, we have previously characterized some proteins, such as PTMA ( Venditti and Minucci, 2017 ; Minucci and Venditti, 2022 ; Venditti et al, 2022 ), and two cytoskeleton-related proteins, DAAM1 ( Minucci and Venditti, 2022 ; Pariante et al, 2016a ; Venditti et al, 2020b ; c ; Venditti et al, 2021a ) and PREP ( Santillo et al, 2019 ; Venditti and Minucci, 2019 ; Venditti et al, 2020b ; Venditti et al, 2021a ; Minucci and Venditti, 2022 ), in the testis, suggesting their involvement in the proliferative and differentiative stages of gametogenesis. In particular, PTMA, one of the most acidic mammalian polypeptides (3.5 isoelectric point), is an anti-apoptotic factor associated with post-meiotic GC progression and SPZ interaction with the oocyte ( Venditti and Minucci, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many works reporting the effects of environmental pollutants on reproductive physiology have shown that one of the main targets of these substances is exactly the cytoskeleton of testicular cells ( Wang et al, 2020a ; Wang et al, 2020b ; Belgacem et al, 2022 ), and we recently demonstrated that DAAM1 and PREP are specific targets of Cd toxicity ( Chemek et al, 2018 ; Venditti et al, 2020d ; 2021b ), however; to our knowledge, no paper has studied the impact of MP, alone or given in combination with Cd, on DAAM1 and PREP. Regarding PTMA, we recently showed its significant role, as anti-apoptotic factor, in regulating cell cycle progression occurring during normal and/or pathological cell differentiation of mammalian testis ( Venditti et al, 2022 ); but, to date, no evidence demonstrated whether PTMA may be a target of environmental pollutants, as MP and/or Cd.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy and apoptosis can be activated by common signals at the upstream and molecular level, meaning that both processes also share similar pathways linking or separating the cellular responses. Cells can either enter apoptosis or into autophagy as a result of responding to the same type of stressors (Venditti et al, 2022) and the switching between apoptosis and autophagy depends on the stimulus intensity, in fact, cellular homeostasis is disrupted when autophagy becomes defective resulting in the activation of apoptosis. (Andjelkovic et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, PTMA was recently stated to have a pro-autophagic role in human testis. PTMA possibly serves as a switch from apoptosis to autophagy [44]. Therefore, it could also be hypothesized that it links the crosstalk of apoptosis and autophagy in female reproduction.…”
Section: Discussionmentioning
confidence: 99%